Mitochondrial pathology in progressive cerebellar ataxia. Issue 1 (December 2015) - Bargiela, David; Shanmugarajah, Priya; Lo, Christine; Blakely, Emma; Taylor, Robert; Horvath, Rita; Wharton, Stephen; Chinnery, Patrick; Hadjivassiliou, Marios
Abstract Background Mitochondrial disease can manifest as multi-organ disorder, often with neurological dysfunction. Cerebellar ataxia in isolation or in combination with other features can result from mitochondrial disease yet genetic testing using blood DNA is not sufficient to exclude this as a cause of ataxia. Muscle biopsy is a useful diagnostic tool for patients with ataxia suspected of mitochondrial disease. Our aim was to determine specific patient selection criteria for muscle biopsy to see how frequent mitochondrial mutations are responsible for progressive ataxia. We performed a two centre retrospective review of patients with unexplained progressive ataxia who underwent muscle biopsy for suspected mitochondrial disease between 2004 and 2014 (Sheffield and Newcastle Ataxia Centres). Results A total of 126 patients were identified; 26 assessed in Newcastle and 100 in Sheffield. Twenty-four patients had pure ataxia and 102 had ataxia with additional features. The total number of patients with histologically suspected and/or genetically confirmed mitochondrial disease was 29/126 (23 %). Conclusions A large proportion of patients (23 %) with progressive ataxia who underwent muscle biopsy were found to have features of mitochondrial dysfunction, with molecular confirmation in some. Muscle biopsy is a helpful diagnostic tool for mitochondrial disease in patients with progressive ataxia.